Organic-Inorganic Hybrid Green Materials for Soil Improvement - Nawarathna, T.H.K.; Gowthaman, S.; Nakashima, K.; Kawasaki, S. (Springer Nature, 2022)
Weak problematic soils are extensively used for the constructions due to the scarcity of the suitable lands owing to the rapid population growth and industrialization. However, the properties of the weak soils require to be improved prior to the construction to ensure the safety of the infrastructures. Although the chemical grouting is the widely used technique to improve the weak soils, most of the grouting materials are environmentally hazardous. Therefore, biological approaches to create bio-grouting materials have gained much attention recently as an ecofriendly and sustainable technique to treat the weak soils. Among them, polymer modified urease-based bio-cementation has been recognized as a more sustainable and ecofriendly method to produce organic-inorganic biomaterials. Urease-based bio-cementation is a biogeochemical process which is driven by the enzyme urease. It has the capability to produce calcium carbonate artificially by hydrolysis of urea in the presence of calcium source. By incorporation of the polymer to the urease-based bio-cementation, much effective hybrid green biomaterial can be formed rather using only calcium carbonate as a biomaterial. It can effectively bind the soil particles together and can densify the weak foundation soils by efficient filling of the pore spaces. Further, this hybrid material supports to achieve a higher strength, fracture resistance and reduces the brittleness of the bio cemented soils. In this chapter, a short review about the role of the polymer modified urease-based bio-cementation on weak foundation soil improvement is presented.
Keywords: Bio-cementation; Hybrid biomaterial; Polymer; Soil improvement; Urease